ANALISIS DENSITAS LUMPUR STARCH DAN DRISPAC TERHADAP PROSES PENGANGKATAN CUTTING DENGAN MENGGUNAKAN METODE CUTTING TRANSPORT RATIO - Apriandi Rizkina Rangga Wastu; Ridha Husla; Ghanima Yasmaniar; Prayang Sunny Yulia; Mario Valentino Dio; Tedy Subardja (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2023)
The use of the right drilling mud in a drilling well has a good ability to clean the hole so that the process of removing the cutting to the surface can run optimally.. Aim: In this research, we will analyze the physical properties of density mud using starch and Drispac mud samples which are natural. The two mud samples are used to find out whether the two mud samples can carry cuttings optimally. Cutting Transport Ratio is one of the cutting removal methods used in the cutting lifting process using the average speed and slip speed of the mud. The cutting removal process can be said to be successful if it has a percentage of > 50%. Methodology and Results: The starch and Drispac sludge samples will be tested using several temperatures, namely 150°F, 200°F and 250°F. Both samples will be tested for their physical properties, namely the density value. The selected density value is one of the parameters needed in the slip speed calculation process in the cutting lifting process. The density value obtained in the starch mud sample was 8.7-9.1 ppg while in the Drispac sample it was 8.65 - 9 ppg. These results are the initial results obtained, but because the results on the 200°F and 250°F samples are not in accordance with the specifications, an additional barite is needed for each of these samples. Both starch and drispac sludge added 60 grams of barite at a sample temperature of 200°F and 120 grams at a sample temperature of 250°F. The results of the density values ​​obtained when barite was added were 10-10.7 ppg for starch mud samples and 9.9-10.65 ppg for Drispac mud samples. The results of the density test will be carried out by testing the removal of cuttings using the Cutting Transport Ratio. The results obtained for the two samples, for starch sludge, obtained a value of 98.31-99.19% while for drispac mud 98.61-99.18%.m. Conclusions: The increase in temperature causes the value of the filtration loss to decrease because the water content in the filtrate also evaporates, causing the filtration loss to decrease. The mudcake value in this experiment was also influenced by the results of the filtration loss value. The higher the filtration loss value, the thicker the value of the mudcake is due to the large number of precipitated particles.